Quem pariu Mateus que balance? Uma cartografia dos desejos maternais na adolescência CERG-São Félix/BA - Rebouças, Jussiana Silva dos Santos (2017)
School, desires, sexuality, gender and prohibition are some lines that cross adolescence pregnancy, although the knowledge disseminated by the media and professionals of the various areas of knowledge continue to be speeches that emanate the power to silence and deny youth protagonism. In this way, the approach to motherhood in adolescence needs new flavors, mutations, recreations, inventions beyond the hygienist and moralizing speeches that imprison potencies of life. Therefore, the present dissertation has presented a cartography made by many hands, a writing in which researcher, school community and teenage mothers are depersonalized at the same time as they are singled out in the specificities of the experiences, in the reaffirmation of muted voices, in the crossing of the Intensity and visibility of the multiple paths covered. Thus, through narratives about (folding and unfolding) of memory we have been scribbling diaries, participating in group conversations in social networks, exchanging stories and creating relationships. Now, how do adolescents experience mothering, especially regarding school demands? How is (not) desired pregnancy processed in the daily life of these girls between meanings shared with their partners and coercion suffered by social institutions? And finally, who is responsible for Mateus? Such inquiries were amidst the nine months of gestation which, far from representing a linearity of time, constitute deviations, which disarray concepts and deterritorialize immaculate truths.